Kinerja Akademik, Pertimbangan Pasar Kerja, Minat Berkarir Akuntan Publik - Suindari, Ni Made; Purnama Sari, AA Pt. Agung Mirah (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
The development of the number of public accountant in Indonesia has not been proportional to the number of accounting graduate students each year. Public accountant is one of the professional career choises for accounting graduate students. This research was conducted to analyze the effect of academic performance and labor market considerations in the perception of career choice of students majoring in accounting as a public accountant in private university on Denpasar. Previous research on consideration of the labor market shows different results. The population in this study was 2270 peoples and 340 respondents from Unwar, Undiknas, Unhi and Unmas Denpasar. This study uses primary data was collected by using a questionnaire by using convenience sampling methods. Data analysis technique used by multiple linear regression analysis. The result showed that the academic performance and consideration of the labor market has positive effect on the selection of career as a public accountant.